A systematic review of active comparator controlled clinical trials in patients with moderate-to-severe psoriasis. (4th July 2018) - No, Daniel J.; Amin, Mina; Bhutani, Tina; Wu, Jashin J.
Abstract: Purpose: Interleukin (IL)-17 and IL-23 inhibitors are the newest biologic agents used in the management of moderate-to-severe psoriasis. Active comparator studies allow for direct comparison of different biologic agents. We sought to systematically investigate the efficacy of newer biologic agents compared to earlier biologics. Materials and methods: We conducted a literature search for randomized control trials that compared the efficacy of a biologic agent with an active comparator. Articles from January 1 2010 to June 26 2017 were searched. Reference lists were also reviewed for studies for inclusion. Results: Twelve studies were included, a majority being phase III trials. All of the studies compared the efficacy of IL-17 and IL-23 inhibitors with adalimumab, etanercept, or ustekinumab with the exception of one study that compared the efficacy of ustekinumab with etanercept. IL-17 and IL-23 inhibitors consistently demonstrate superior efficacy over TNF inhibitors and ustekinumab as assessed by 75%, 90%, and 100% improvement in baseline Psoriasis Area and Severity Index (PASI) scores at week 12. Conclusions: Overall, IL-17 and IL-23 inhibitors appear to demonstrate superior efficacy and more rapid clinical improvement when compared to older biologic agents. This review may help predict patient outcomes, manage patient expectations, and biologic agent utilization.